Daylight Quality Evaluation for Boarding House Design in Malang Indonesia - Ernaning, Setiyowati; Gautama, Achmad Gat; Wismantara, Pudji Pratitis (Proceeding of International Conference on Engineering, Technology, and Social Sciences (ICONETOS); Vol 2 No 1 (2020): The 2nd International Conference on Engineering, Technology, and Social Sciences, 2021)
The objective of this paper is to calculate and evaluate the daylight quality of the boarding house design typology in Malang, Indonesia. The method is field measurement using digital lux meter tool. The measurement is done in some boarding houses in Malang with different room design configuration. The research objects are boarding houses in U, I, and L letter form, and also a square form with a void in the middle. The result shows that the daylight quality in U, L, and square form is around 100-200 lux. It is suitable for daylight illumination standar for bedroom if the room is for rest or sleep only. If the bedroom function is also for study or read, then the daylight illumination is far from the requirement. The daylight illumination for the study room is minimum 300 lux. The worst form that only provide low quality of daylight is I form.